Curating the CIA World Factbook - Peter Buneman; Heiko MÃ¼ller; Chris Rusbridge (International Journal of Digital Curation, 2009)
The CIA World Factbook is a prime example of a curated database â€“ a database that is constructed and maintained with a great deal of human effort in collecting, verifying, and annotating data. Preservation of old versions of the Factbook is important for verification of citations; it is also essential for anyone interested in the history of the data such as demographic change. Although the Factbook has been published, both physically and electronically, only for the past 30 years, we appear in danger of losing this history. This paper investigates the issues involved in capturing the history of an evolving database and its application to the CIA World Factbook. In particular it shows that there is substantial added value to be gained by preserving databases in such a way that questions about the change in data, (longitudinal queries) can be readily answered. Within this paper, we describe techniques for recording change in a curated database and we describe novel techniques for querying the change. Using the example of this archived curated database, we discuss the extent to which the accepted practices and terminology of archiving, curation and digital preservation apply to this important class of digital artefacts.